Assessing Student Engagement in A Mobile-Assisted Academic Writing - Misdi Misdi; Nurani Hartini; Anna Tambunan (Universitas Cokroaminoto Palopo, 2021)
A rapid ease of mobile-learning use in higher education has excessively driven both university teachers and student-researchers to work more effective and efficient, especially in their academic writing tasks. Yet, albeit a number of studies in this area, most studies focused on their writing skills. Little has been reported how mobile-assisted academic writing has impacted on student-researchers’ sense of empowerment. Thus, this paper attempts to share my investigation on how mobile-assisted academic writing and supervision practices has impact on the student-researchers’ psychological empowerment. Sixteen out of 45 student-researchers from a private English college in Indonesia were recruited and voluntarily participated in a 12 week academic writing projects. The data were gathered from closed-ended questionnaire and interview. The results shows that the adoption of mobile-assisted academic writing has positive impacts of the student-researchers’ psychological empowerment. The student-researchers felt comfortable to have online immediate feedback and thus, built sense of friendly supervision. In addition, the findings also revealed that this supervision mode makes the student-researchers to be reflective learners